Fábrica de calzados Prestancia: ¿los negocios "perros" siempre se descontinúan? - Villajuana, Carlos (2006)
The general manager of a shoe factory is advised by the marketing manager to discontinue a line with very little relative market share in a slow growth market and for which prices are below total unit production costs. Before making a decision, the general manager decides to retain a consultant to give him a broader view of the situation. The consultant provides new elements of judgment for the reader to ponder.